Obese outbred mice only partially benefit from diet normalization or calorie restriction as preconception care interventions to improve metabolic health and oocyte quality. Issue 12 (7th November 2022) - Smits, A; Marei, W F A; Moorkens, K; Bols, P E J; De Neubourg, D; Leroy, J L M R
Abstract: STUDY QUESTION: Can diet normalization or a calorie-restricted diet for 2 or 4 weeks be used as a preconception care intervention (PCCI) in Western-type diet-induced obese Swiss mice to restore metabolic health and oocyte quality? SUMMARY ANSWER: Metabolic health and oocyte developmental competence was already significantly improved in the calorie-restricted group after 2 weeks, while obese mice that underwent diet normalization showed improved metabolic health after 2 weeks and improved oocyte quality after 4 weeks. WHAT IS KNOWN ALREADY: Maternal obesity is linked with reduced metabolic health and oocyte quality; therefore, infertile obese women are advised to lose weight before conception to increase pregnancy chances. However, as there are no univocal guidelines and the specific impact on oocyte quality is not known, strategically designed studies are needed to provide fundamental insights in the importance of the type and duration of the dietary weight loss strategy for preconception metabolic health and oocyte quality. STUDY DESIGN, SIZE, DURATION: Outbred female Swiss mice were fed a control (CTRL) or high-fat/high-sugar (HF/HS) diet. After 7 weeks, some of the HF mice were put on two different PCCIs, resulting in four treatment groups: (i) only control diet for up to 11 weeks (CTRL_CTRL), (ii) only HF diet for up to 11 weeks (HF_HF), (iii) switch at 7 weeks from an HF to an ad libitum control diet (HF_CTRL) and (iv) switch at 7 weeks from an HF to a 30% calorie-restricted control diet (HF_CR) for 2 or 4 weeks. Metabolic health and oocyte quality were assessed at 2 and 4 weeks after the start of the intervention (n = 8 mice/treatment/time point). PARTICIPANTS/MATERIALS, SETTING, METHODS: Changes in body weight were recorded. To study the impact on metabolic health, serum insulin, glucose, triglycerides, total cholesterol and alanine aminotransferase concentrations were measured, and glucose tolerance and insulin sensitivity were analyzed at PCCI Weeks 2 and 4. The quality of in vivo matured oocytes was evaluated by assessing intracellular lipid droplet content, mitochondrial activity and localization of active mitochondria, mitochondrial ultrastructure, cumulus cell targeted gene expression and oocyte in vitro developmental competence. MAIN RESULTS AND THE ROLE OF CHANCE: Significant negative effects of an HF/HS diet on metabolic health and oocyte quality were confirmed ( P < 0.05). HF_CTRL mice already showed restored body weight, serum lipid profile and glucose tolerance, similar to the CTRL_CTRL group after only 2 weeks of PCCI ( P < 0.05 compared with HF_HF) while insulin sensitivity was not improved. Oocyte lipid droplet volume was reduced at PCCI Week 2 ( P < 0.05 compared with HF_HF), while mitochondrial localization and activity were still aberrant. At PCCI Week 4, oocytes from HF_CTRL mice displayed significantly fewer mitochondrial ultrastructural abnormalities and improved mitochondrial activity ( P < 0.05), while lipid content was again elevated. The in vitro developmental capacity of the oocytes was improved but did not reach the levels of the CTRL_CTRL mice. HF_CR mice completely restored cholesterol concentrations and insulin sensitivity already after 2 weeks. Other metabolic health parameters were only restored after 4 weeks of intervention with clear signs of fasting hypoglycemia. Although all mitochondrial parameters in HF_CR oocytes stayed aberrant, oocyte developmental competence in vitro was completely restored already after 2 weeks of intervention. LARGE SCALE DATA: N/A. LIMITATIONS, REASONS FOR CAUTION: In this study, we applied a relevant HF/HS Western-type diet to induce obesity in an outbred mouse model. Nevertheless, physiological differences should be considered when translating these results to the human setting. However, the in-depth study and follow-up of the metabolic health changes together with the strategic implementation of specific PCCI intervals (2 and 4 weeks) related to the duration of the mouse folliculogenesis (3 weeks), should aid in the extrapolation of our findings to the human setting. WIDER IMPLICATIONS OF THE FINDINGS: Our study results with a specific focus on oocyte quality provide important fundamental insights to be considered when developing preconception care guidelines for obese metabolically compromised women wishing to become pregnant. STUDY FUNDING/COMPETING INTEREST(S): This study was supported by the Flemish Research Fund (FWO-SB grant 1S25020N and FWO project G038619N). The authors declare there are no conflicts of interest.